First Language Acquisition by Roma and Slovak Children - Samko, Milan; Čerešník, Michal; Čerešníková, Miroslava (East European Journal of Psycholinguistics, 2021)
The study analyzes the context and relationships of the progress in first language acquisition by monolingual children (First language: Slovak) and Roma-Slovak bilingual children (First language: Romani), as determined by the type of Roma community in which individual children live. We conducted the research in two phases, the first at the beginning of the school year (test) and the second at the end of the school year (post-test). The OOS image-vocabulary test as a psychological toolwas used for examining children’s vocabulary and a certain dimension of their readiness for school. The standardized O-S-S tool is structured to include 30 colorful images illustrating objects, animals, and activities, which are presented to children on an individual basis (Kondáš, 2010). For the purposes of the study, the test was modified and culturally adapted for Roma children with a pairing of Romani and Slovak languages. The research set in total consists of (n = 135) children in their first year of schooling and is separated into Roma children with L1: Romani (n = 68) and Slovak children with L1: Slovak (n = 67). Subsequently, the research set of Roma children (n = 68) belong to 3 types of communities. These 3 types of communities are the following: type 1: municipal and urban concentrations (n = 22); type 2: settlements located on the outskirts of a city or municipality (n = 23); and type 3: settlements spatially remote or separated by a natural or artificial barrier (n = 23). To analyze the data statistically, we used the SPSS 20.0 statistical program. The results shown statistically significant differences in L1 comprehension between Roma-Slovak bilingual children from type 1, type 2, and type 3 Roma communities and, additionally, between monolingual children at the beginning and at the end of the school year. According to the first measurement at the beginning of the school year (test) and the second measurement at the end of the school year (post-test) in L1 in the case of verbs and nouns, the highest success rate was achieved by monolingual Slovak children, followed by Romani-Slovak bilingual children from type 1 communities, followed by children from type 2 communities, and the lowest success rate was achieved by children from type 3 communities. The main research problem arising from the findings is that the progress in first language acquisition by Roma-Slovak bilingual children is determined by the type of Roma community in which the child lives. Acknowledgments This paper is an output of the research project “Language and Communication Problems in Slovakia and their Management” funded by the Slovak Research and Development Agency under the contract No. APVV-17-0254 (2018 – ). It is the continuation of the research project “Language competence of the Romani pupils in the first grade of primary school” funded by the same agency under the contract No. VEGA 1/0845/15 (2015–2017).